A sustainable electrical interface to mitigate emissions due to power supply in ports. (February 2016) - Coppola, T.; Fantauzzi, M.; Lauria, D.; Pisani, C.; Quaranta, F.
Abstract: The paper presents a proposal of an innovative sustainable power supply solution for seaports with the related design and control. This solution differs from the classical solution for the presence of a smart electrical interface composed by two basic components: the first one, a rotating converter-instead of the widely used static converter-that ensures higher and therefore much more detectable short-circuit currents; the second, an advanced static var compensator specifically designed for enhancing power quality issues and hence favoring the seaport connection to the main grid for cold ironing applications. The designed control strategy for the tailored power supply solution is proven successful and effective by the numerical applications reported in the last part of the paper.